(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the affairs of register of the population in Uzbekistan SSR are defined (Soviet Socialist Republic) in 1937.Through the conclusion of the register of the population the economical, social, and political life is planned to the next decades in this place